Tetranectin and Paraoxonase 1 in Patients with Varying Stages of Heart Failure: A Cross-Sectional Analysis - Paula Alexandra Vulciu; Luminita Pilat; Maria-Daniela Mot; Voicu Dascau; Calin Daniel Popa; Norberth-Istvan Varga; Maria Puschita (Clinics and Practice)
Background: Heart failure (HF) is a leading cause of mortality across the globe, prompting ongoing research into novel biomarkers for improved risk stratification and patient management. Methods: This cross-sectional study aimed to investigate the relationship between two promising biomarkers, tetranectin and paraoxonase 1, and the severity of heart failure in a cohort of 87 patients with cardiovascular risk factors. Participants were categorized into three groups based on their New York Heart Association (NYHA) classification: no HF (Control), NYHA class I (G1), and NYHA class II-IV (G2). Results: Our analysis revealed a stepwise decrease in both TETRA and PON1 levels with increasing HF severity, with the Control group exhibiting the highest levels and the G2 group the lowest. Interestingly, a significant positive correlation between TETRA and PON1 was observed only in the Control group, suggesting a potential interplay between these biomarkers in healthy individuals that may be disrupted with the onset of HF. Furthermore, both TETRA and PON1 were positively associated with left ventricular ejection fraction (LVEF) and negatively associated with diastolic dysfunction, indicating their potential involvement in both systolic and diastolic cardiac function. Conclusions: These findings suggest that TETRA and PON1 may serve as valuable biomarkers for assessing HF severity and prognosis. Further research is warranted to validate these findings in larger, prospective studies and to explore their clinical utility in guiding treatment decisions.